Freedom Fit for a Feminist? On the Feminist Potential of Quentin Skinner's Conception of Republican Freedom. Issue 1 (1st April 2014) - Halldenius, Lena
Abstract The aim of this paper is to make it credible that there are feminist reasons for being a republican about freedom. In focus is Quentin Skinner's conception of republican, or "neo-Roman", freedom. Republican theory in history has not excelled in making poverty, gender hierarchy, and racism within the republic into main sources of concern. So can there be a radical republican theory of liberty fit for a feminist, to make sense of arbitrary power in the every day life of work, households, and local communities, where power is vague and unorganized? Proceeding from three questions – What does freedom mean? Under what circumstances does the issue arise? Why should we care? – I argue that in a feminist republicanism the lived experience of the unfree will have primary and not, as Skinner now suggests, secondary importance. A feminist republican will be particularly concerned not only with what unfreedom is but with what it is like.